Optimasi Komposisi Pakan Kambing Boer Menggunakan Algoritme Evolution Strategies - Ramadhan Anindya Guna Aniwara; Nurul Hidayat; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The common problem that mostly happened in animal husbandry of goat is the insufficient usage of fodder. A simple mistake in choosing the fodder caused the goat to having a little nutrition in their body. That surely make the goat not growing breed well. In the economic point of view, the purchase of fodder becomes the highest cost in factory farming, so the cost should be reduced as low as possible to maximize the revenue. Optimizing the preparations of goat's fodder is a way to reducing the cost, that can also increasing the revenue. In this case, a evolution strategies algoritm is used to optimizing the goat's fodder. The type of ES process used is (Î¼ / r + Î») so that the reproduction process involves recombination and the mutation result will be included with the parent in the selection and selection process using elitism selection. The optimal solution is obtained from population size of 90 and the number of generations 100 obtained the highest average fitness value of 0.803. The final result is recommendation of goat's fodder.